Multiple Colletotrichum species commonly exhibit focal effector accumulation in a biotrophic interface at the primary invasion sites in their host plants. (3rd October 2021) - Ogawa, Taiki; Chen, Jinlian; Mise, Kazuyuki; Takano, Yoshitaka
ABSTRACT: Fungal plant pathogens deploy a suite of secreted proteins, called effectors, to facilitate successful infection. Several fungal pathogens have been reported to secrete and accumulate their effector proteins in the host–pathogen interfacial spaces. Previously, we reported that the strain 104-T of the cucurbit anthracnose pathogen Colletotrichum orbiculare secretes and accumulates mCherry-tagged effectors along with the formation of ring-shaped fluorescence signals beneath the appressoria. However, it was unclear whether these effector accumulation patterns occur in other C. orbiculare isolates and other species belonging to the Colletotrichum genus. Here, we investigated the effector localization during host infection of C. orbiculare MAFF306589, C. trifolii MAFF305078, which infects alfalfa, and C. higginsianum MAFF305635, which infects Brassicaceae plants. We generated effector–reporter lines of each species, which constitutively expressed mCherry-tagged CoDN3 effector (CoDN3:mCherry). Immunoblotting analysis of the liquid culture fluids of the generated lines detected CoDN3:mCherry, which confirmed secretion of CoDN3:mCherry by fungal cells. Via inoculation assays in the corresponding host plants, we detected ring-shaped CoDN3:mCherry fluorescence around the appressorial invasion sites in all tested reporter lines. These results suggest that pathogens in the Colletotrichum genus have evolutionarily conserved the trait of effector secretion in the infection stage irrespective of differences in their hosts.